KREATIVITAS GURU DALAM MERDEKA BERMAIN DI PAUD DESA PURWASARI DARMAGA KABUPATEN BOGOR - Helwiyah Makarim; Siti Fatima; Sri Hayati; Suhermi (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2023)
The purpose of this study is to increase teacher creativity in teaching quality comprehensively, so that teachers provide more space for independence based on the needs and achievements of early childhood, because independent play in early childhood education is learning by emphasizing play and exploring something with joy. , fun and cheerful. The research subjects were PAUD teachers in the Purwasari village area, Dramaga sub-district, Bogor district, namely Mentari PAUD totaling 5 people and Nurul Hikmah PAUD totaling 5 people. Data collection techniques used observation, giving questionnaires and in-depth interviews ((deep interviews). The results showed that creativity was not maximized due to a lack of understanding of the substance of the regulations on PAUD, and a teacher must always be explored and learn to adapt to needs. Developing imagination power as well as providing closeness to early childhood.